Pelatihan Kreasi Pembelajaran Tari Bagi Guru Seni Budaya di Bandar Lampung - Goesthy Ayu Mariana Devi Lestari; Agung Kurniawan; Ricky Marwan Putra (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2022)
The Covid 19 pandemic period presented challenges to all areas of life, including the education sector. The learning process in Indonesia had to be incidentally diverted towards online learning. Constraints and challenges are faced especially for practical learning characteristics, such as arts and culture subjects with main topics such as dance. To get around this, it is necessary to motivate the creativity of arts and culture teachers through training in the creation of art learning, especially dance learning. This activity instills knowledge and skills for teachers to be creative in developing dance learning in arts and culture subjects. This is present as a joint solution in seeking to keep the arts and culture learning process running and the final competence of students can be achieved as expected. The training method is carried out using lecture techniques, discussions and online practice. Through this training, 60% of the participants are confident in designing Blended Learning art and culture learning with more interesting learning media. This activity can help these teachers to design creative and informative learning media with an average achievement of 84.85 which is classified as